Perbandingan CD4 HIV –TB Paru Sebelum dan Sesudah ARV dan OAT - Cesia, Trivania; Hasibuan, Pantas; Silaen, Johan Christian (LPPM Universitas HKBP Nommensen, 2022)
Human Immunodeficiency Virus (HIV) is a viral infectious disease that attacks the immune system or white blood cells (lymphocytes). HIV, which belongs to the Retroviridae family, is lymphatic, which can damage the specific immune system, namely T-helper lymphocytes or Cluster of Differentiation 4 (CD4). The CD4 count is normal when it is 500–1400 cells/mm3, which is usually the determinant of whether a patient is infected with HIV or not. This study aims to assess the comparison of CD4 counts in HIV-TB patients before and after ARV and OAT treatment at Dr. Pirngadi Medan City. Observational analysis research with a cross-sectional design was conducted at RSUD Dr. Pirngadi Medan City in September 2022. The sample for this study was 20 patient records from the medical records of RSUD Dr. Pirngadi, Medan City. The data were analyzed using an unpaired t-test. The results of the study showed that the most HIV-TB pulmonary patients at RSUD Dr. Pirngadi Medan City were aged 36-45 years (50.0%). The majority of male patients (90.0%) and the domicile of most patients in Medan City are in the Medan Tembung sub-district (15.0%). The results of the unpaired t-test obtained a p-value of 0.022, meaning that there was a significant difference between the CD4 count before and after ARV and OAT treatment in HIV-TB patients at RSUD Dr. Pirngadi Medan City. There were significant differences in CD4 counts before and after ARV and OAT treatment in HIV patients with pulmonary TB co-infection at Dr. Pirngadi, Medan City.